Effect of Operational Audit and Internal Control of Employee Performance - Rima Ayu Aryanti; Dedy Sudarmadi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the Effect of Operational Audit and Internal Control on Employee Performance at PT. Anggana Kurnia Putra. The data used are primary data distributed in the form of a distributed questionnaire to employees of PT. Anggana Kurnia Putra. This study uses a hypothesis testing model starting from the validity test, reliability test, method of successive interval, classic assumption test, multiple linear regression analysis, coefficient of determination, and t test. This analysis is based on data from 44 respondents who have completed all statements in the questionnaire. The results of the study show that: (1) Operational Audit influences Employee Performance at PT. Anggana Kurnia Putra. This means that most employees are satisfied with the implementation of Operational Audit at PT. Anggana Kurnia Putra is thus effective and can improve Employee Performance at the company. (2) Internal Control influences Employee Performance at PT. Anggana Kurnia Putra. This means that the standards of regulation or control that have been set by the Company can be followed and adhered to properly by employees of PT. Anggana Kurnia Putra thus improving Employee Performance in the company.